Associations Between Maladaptive Perfectionism and Life Satisfaction Among Chinese Undergraduate Medical Students: The Mediating Role of Academic Burnout and the Moderating Role of Self-Esteem - Wang, Qinghua; Wu, Huazhang (Frontiers in Psychology, 2022)
Empirical research has shown that maladaptive perfectionism may lead to lower life satisfaction. However, the relationship between maladaptive perfectionism and life satisfaction among medical students and the mechanism underlying this relationship still need to be further explored. The present study used a large sample of undergraduate medical students to examine the associations between maladaptive perfectionism and life satisfaction and to explore the mechanism underlying the associations. Specifically, the present study tried to probe the mediating role of academic burnout and the moderating role of self-esteem in the relationship between maladaptive perfectionism and life satisfaction in medical students. We invited 1628 undergraduate medical students from two medical universities in Northeastern China to participate in the survey. Among the students recruited, 1377 medical students (response rate: 84.6%) completed questionnaires including the Frost Multidimensional Perfectionism Scale (FMPS) maladaptive perfectionism subscales, the Chinese College Student Academic Burnout Inventory (CCSABI), the Satisfaction With Life Scale (SWLS), the Rosenberg Self-Esteem Scale (RSES) and demographic information. Results show that maladaptive perfectionism was significantly negatively related to life satisfaction among medical students and academic burnout played a significant mediating role (β = -0.10, BCa 95%CI: -0.12, -0.07) in this relationship. Moderated mediation analyses reveal that the mediating effect of maladaptive perfectionism on life satisfaction via academic burnout was moderated by self-esteem. Maladaptive perfectionism exerted a stronger effect on life satisfaction via the mediating role of academic burnout for medical students with high self-esteem (β = -0.026, SE = 0.009, 95%CI = [-0.047, -0.011]) than for medical students with low self-esteem (β = -0.019, SE = 0.009, 95%CI = [-0.038, -0.001]). Medical institutions can implement effective interventions to decrease medical students’ maladaptive perfectionism levels and academic burnout levels, and increase their self-esteem levels in order to enhance their life satisfaction.